It's all about what you do - Kevin Stolarick (Oz, 2010)
In the Spring of 2001, I sat in Richard Florida’s kitchen poring over a list with him. “Yes, no, no, obviously, ..., of course, nope, nada, none of those, don’t think so, ..., Yes, what do you think? ...” Item by item, we looked through the Bureau of Labor Statistic’s Standard Occupational Codes’ occupation titles and identified the creative class.